Modalitas Belajar pada Pembelajaran Geografi: Tinjauan Literatur dan Implikasinya terhadap Pembelajaran - Manek , Agustinus Hale; Sunimbar, Sunimbar; Ersani, Erry (Universitas Pendidikan Ganesha, 2025)
Geography learning can encourage and inspire students to think critically, analytically, and creatively in identifying, understanding, and solving problems. Geography learning involves differences in student characteristics in absorbing and processing information. However, learning effectiveness can be influenced by understanding according to student characteristics, especially related to the learning modality used in absorbing information. This article aims to examine in depth the role of learning modalities in geography learning, as well as assess the effectiveness of modalities in learning. The method used in writing this article is a literature review of various literature by analyzing various sources relevant to the learning topic and learning styles. The results of the study found that geography learning that integrates various modalities in a multimodal manner is more effective in improving conceptual understanding in learning. Therefore, contextual, adaptive, and experienced geography learning is highly recommended to accommodate the diversity of student characteristics and encourage the optimal achievement of 21st-century competencies.